The hypothesis of the functional disintegration of the brain due to the persistence of benign epileptiform patterns on the electroencephalogram - I. A. Sadekov; A. V. Polyakov; I. V. Sadekova; E. A. Tupikina; V. Yu. Kochmar; T. V. Termenzhi (Русский журнал детской неврологии)
In this work, we have analyzed the results of observation of 200 children aged from 3 to 15 years old, who had various neuropsychiatric disorders in combination with benign childhood epileptiform patterns on the electroencephalogram. A hypothesis has been put forward about functional disorders of the developing nervous system with prolonged persistence of benign focal epileptiform discharge of childhood on electroencephalogram, mainly in slow-wave sleep. The possibilities of therapeutic correction of these disorders are discussed.